EXPERT APPROACHES TO EQUIVALENCE EVALUATION OF DRUGS — ANALOGUES OF ENDOGENOUS COMPOUNDS AS CONSISTENT WITH THE RUSSIAN LEGISLATION AND INTERNATIONAL LAW - D. P. Romodanovsky; D. V. Goryachev; A. P. Solovieva; I. V. Kokin; N. N. Eremenko (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article demonstrates that bioequivalence studies of generic drugs whose active substances are analogues of endogenous compounds found in the human body in natural concentrations present a major challenge as compared to other products and call for a specific regulatory approach. In the absence of available scientific data demonstrating that the product intake can increase the general concentration of the endogenous compound, conducting bioequivalence studies can be economically impractical in contrast to a standard comparative clinical trial, because first it would be necessary to demonstrate a significant increase in the compound concentration in blood plasma. The article analyses Russian legislation and international law with respect to evaluation of medicinal products that are analogues of endogenous compounds, i.e. vitamins, hormones, enzymes, amino acids and salts. It was demonstrated that correction for endogenous compound concentration in blood plasma and control of its dietary intake are required in order to obtain accurate bioequivalence results. The article summarises the experience gained at the FSBI «SCEEMP» of the Ministry of Health of the Russian Federation with respect to evaluation of medicines that are analogues of endogenous compounds, and outlines the most frequent mistakes in testing protocols. It substantiates the need for an individual approach tailored for each particular product, since there is no single solution to the problem of background concentration of endogenous compounds. The authors of the article developed some key solutions that can help minimize the impact of background concentrations of test samples on the results of bioequivalence assessment. Based on the results of the analysis performed and accumulated experience the authors of the article suggested some ways to resolve the problem.